(untitled) (Journal of responsible AI & ethics, 2026)
The advent of Artificial Intelligence (AI) has revolutionized industries and societies around the world, offering advancements in technology, automation, and decision-making processes. However, as AI becomes increasingly integrated into global systems, it has raised critical ethical concerns, particularly regarding cultural representation and biases embedded within AI algorithms. This paper explores the cultural impacts of AI, focusing on how AI systems might perpetuate cultural biases, exclude underrepresented communities, and fail to ensure ethical representation. Drawing upon case studies, empirical research, and theoretical frameworks, the paper examines the role of cultural diversity in AI design, development, and implementation. It also addresses the importance of ethical AI governance that incorporates diverse perspectives to create inclusive, equitable, and responsible systems. The study suggests that ethically guided AI systems that reflect global cultural diversity can lead to more inclusive technologies. It concludes by offering policy recommendations and strategies to ensure that AI systems are developed with ethical representation that respects cultural differences and promotes social justice.